Activation method of sodium-based silicate material as positive electrode of lithium-source-free lithium ion battery and application of sodium-based silicate material in lithium ion battery

By performing sodium-based silicate material activation method on sodium-containing electrode materials, using step voltage charging and discharge and cyclic voltammetry technology, the problems of chaotic charging curve and poor capacity performance in the positive electrode of lithium-ion batteries are solved, and efficient electrochemical performance improvement and cost reduction are achieved.

CN119601606AActive Publication Date: 2025-03-11HARBIN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411787085.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-11
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

When the sodium-containing electrode material is directly used as the positive electrode of a lithium-ion battery, there are problems such as disordered charging curve and poor capacity performance, and it cannot be directly applied.

Method used

The sodium-based silicate material is used as the activation method for the positive electrode of lithium-ion battery without lithium source. By mixing the sodium-based silicate material, conductive agent and binder, adding N-methylpyrrolidone to form a slurry, and activated by step voltage charging and discharge and cyclic voltammetry technology.

Benefits of technology

The capacity and circulation performance of sodium-based silicate materials are effectively improved, so that they exhibit electrochemical performance comparable to lithium-based silicates, overcome the problems of charging curve disorder and poor capacity performance, reduce costs, reduce resource waste, and achieve greening and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601606A_ABST
    Figure CN119601606A_ABST
Patent Text Reader

Abstract

The invention relates to an activation method of a sodium-based silicate material as a positive electrode of a lithium-source-free lithium ion battery and application of the sodium-based silicate material in the lithium ion battery. The invention belongs to the field of electrochemistry. The problems that in the prior art, a sodium-containing electrode material directly serves as a lithium ion battery positive electrode, a charging curve is disordered, and the capacity performance is poor, and consequently application cannot be achieved are solved. According to the activation method disclosed by the invention, the sodium-based silicate material can be used as the positive electrode of the lithium-source-free lithium ion battery, and the sodium-based silicate material is subjected to sodium removal activation by combining repeated stepped charging with a cyclic voltammetry technology, so that the charging curve disorder of the sodium-based silicate material as the positive electrode of the lithium-source-free lithium ion battery is overcome; the problem that the sodium-based silicate material replaces a lithium source material to become a novel lithium-source-free lithium ion battery positive electrode material is solved, the cost is effectively reduced, and the environmental pollution is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrochemistry, and specifically relates to an activation method of a sodium-based silicate material as a positive electrode of a lithium-source-free lithium-ion battery and an application of the sodium-based silicate material in the lithium-ion battery. Background Art

[0002] Secondary batteries can be used repeatedly by activating active substances to produce chemical reactions through charging, so they are regarded as one of the environmentally friendly energy sources. Among them, lithium-ion batteries with high energy density, long service life, energy saving and environmental protection are widely favored by everyone. Positive electrode material is one of the key materials of lithium-ion batteries. With the application demand for increased battery specific capacity, the transition from the initial ternary materials to high nickel and other materials has gradually occurred. Although high nickel materials have high specific capacity, they are still unsatisfactory in terms of safety and stability. Therefore, positive electrode materials with high specific energy density, long cycle life, high voltage and other characteristics will gradually become the focus of research.

[0003] Polyanionic compound materials have the advantages of rich variety, diverse structure, adjustable working voltage, good cycle stability, etc., and are potential ideal positive electrode materials for the development of low-cost environmentally friendly secondary batteries. Among them, the iron-based silicate positive electrode (A2FeSiO4, A=Li or Na) has a dual lithium / sodium structure and a multi-electron reaction system constructed by variable valence transition metals, with a theoretical capacity of up to 272-330mAh / g, and is one of the most promising materials for improving the energy density of energy storage devices. The lithium-containing materials in lithium-ion batteries mainly come from the positive electrode and the electrolyte, which makes the demand for lithium resources in today's society gradually increase, resulting in the continuous increase in the production cost of lithium-ion batteries. However, lithium resources are unevenly distributed in the earth's crust and have limited reserves. 70% of the world's lithium is in South America. It is noted that sodium-containing electrodes also follow the similar intercalation and deintercalation working principle of lithium-ion batteries. If sodium-containing electrode materials can be used as positive electrodes for lithium-ion secondary batteries without lithium sources, the demand for lithium sources can be significantly alleviated. Sodium resources are widely distributed in the earth's crust and have abundant reserves. They are completely unrestricted by resource reserves and geographical distribution, with low costs and less environmental pollution. However, sodium-containing electrode materials cannot be directly used as positive electrodes of lithium-ion batteries due to problems such as disordered charging curves and poor capacity performance. Therefore, developing an activation method that allows sodium-containing electrode materials to be directly used as positive electrodes of lithium-ion batteries is of great significance to economic development, scientific progress and cost savings. Summary of the invention

[0004] The purpose of the present invention is to solve the problem that sodium-containing electrode materials can not be used directly as positive electrodes of lithium-ion batteries due to disordered charging curves and poor capacity performance. The present invention provides a method for activating sodium-based silicate materials used as positive electrode materials for lithium-ion batteries without lithium sources.

[0005] The technical solution of the present invention is as follows:

[0006] One of the purposes of the present invention is to provide a method for activating a sodium-based silicate material as a positive electrode of a lithium-ion battery without a lithium source, and the specific activation steps are:

[0007] S1: Mix the sodium-based silicate material, conductive agent and binder evenly, add N-methylpyrrolidone, stir thoroughly to form a slurry, evenly coat it on aluminum foil, and assemble it into a button battery after drying as the positive electrode and the metal lithium sheet as the negative electrode;

[0008] S2: charge with current I1, voltage range V1-V2, set x step voltages between V1-V2, constant voltage time of each step voltage is T1, then discharge with current I1, repeat n1 times;

[0009] S3: The battery after S2 is subjected to cyclic voltammetry in an electrochemical workstation, with the open circuit voltage as the starting point, a scan rate of γ1 is set, and a forward scan is performed n2 times in the voltage range of V3-V4 to a cut-off voltage of V4.

[0010] It is further defined that the general structural formula of the sodium-based silicate material in S1 is Na2MSiO4, wherein M is at least one of Fe, Mn, Al, Co, Ni, Ti, Cu, Mg or Zn.

[0011] It is further defined that the mass ratio of the sodium-based silicate material, the conductive agent and the binder in S1 is 5-20:1-2:1.

[0012] It is further defined that in S2, 0.2C≤I1≤2C, 1.5V≤V1<V2≤5.0V.

[0013] It is further defined that T1 in S2 is 15-60 min.

[0014] It is further limited that in S2, 1≤n1≤3, 2≤x≤4.

[0015] It is further defined that in S3, 0.1 mV / s≤γ1≤5 mV / s, 1.5 V≤V3≤2.0 V, 4.0 V≤V4≤4.8 V. It is further defined that in S3, 1≤n2≤5.

[0016] The second object of the present invention is to provide a method for activating the above sodium-based silicate material as a positive electrode of a lithium-free lithium-ion battery to prepare a positive electrode material for a lithium-free lithium-ion battery.

[0017] The third object of the present invention is to provide an application of the above-mentioned lithium-source-free lithium-ion battery positive electrode material in a lithium-source-free lithium-ion battery.

[0018] Compared with the prior art, the specific advantages of the present invention are as follows:

[0019] (1) The sodium-based silicate material selected in the present invention is a polyanion compound with a two-electron reaction, which has a high theoretical capacity and is cheap and safe. The activation method of the sodium-based silicate material of the present invention is the first proposed activation method based on lithium-free insertion and extraction positive electrode materials. The activation method of the present invention can effectively improve the capacity and cycle performance, and the activation method of the present invention can make the sodium-based silicate material exhibit electrochemical properties equivalent to those of lithium-based silicates.

[0020] (2) The sodium-based silicate material activation method of the present invention can enable the sodium-based silicate material without a lithium source to overcome the problems of disordered charging curve and poor capacity performance, thereby greatly saving the use of positive lithium source in lithium-free lithium-ion batteries, effectively reducing costs, reducing resource waste, and achieving greening and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a typical step-type constant voltage charge and discharge curve;

[0022] Figure 2 It is a typical cyclic voltammetry step curve;

[0023] Figure 3 This is a charge and discharge curve diagram of 100 times of a lithium-ion battery without a lithium source after the sodium-based silicate material is activated in Example 2;

[0024] Figure 4 This is a charge and discharge curve diagram of 100 times of a lithium-ion battery without a lithium source after the sodium-based silicate material is activated in Example 4;

[0025] Figure 5 The first two charge and discharge curves of the lithium-ion battery without lithium source made of unactivated sodium-based silicate material in Comparative Example 1;

[0026] Figure 6 This is a charge and discharge curve diagram of 100 times of the sodium-based silicate material lithium-ion battery without lithium source that was only subjected to cyclic voltammetry treatment in Comparative Example 3. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0028] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0029] Embodiment 1:

[0030] S1: Mix 0.96g Na2FeSiO4, 0.12g conductive agent acetylene black and 0.12g binder polyvinylidene fluoride, add 10mL N-methylpyrrolidone, and stir thoroughly to form a uniform slurry; then use a scraper to evenly coat it on a clean aluminum foil, vacuum dry it at 110℃ for 24h, and prepare an electrode sheet with a diameter of 16mm as the positive electrode, and finally assemble it with the negative electrode metal lithium sheet in a glove box to form a button battery;

[0031] S2: Charge the battery of S1 at 0.3C current, with a charging voltage range of 1.5-4.6V, set three gradient voltages of 4.2V, 4.4V and 4.6V, and set the constant voltage time to 30min, 30min and 15min respectively, and then discharge it to 1.5V at 0.3C current, and repeat for 3 times;

[0032] S3: Cyclic voltammetry was used on the button cell of S2 in an electrochemical workstation. The open circuit voltage was used as the starting point, and the scan rate was set to 0.5 mV / s. The voltage range was 1.5-4.6 V, and the forward scan was performed 3 times to a cut-off voltage of 4.6 V.

[0033] The electrochemical performance test was carried out, and the test parameters and results are shown in Table 1.

[0034] Embodiment 2:

[0035] S1 is the same as in Example 1;

[0036] S2: Charge the battery of S1 at 0.3C current, with a charging voltage range of 1.5-4.6V, and set three gradient voltages of 4.0V, 4.2V and 4.4V. The constant voltage durations are 30min, 30min and 60min respectively. After charging to a cut-off voltage of 4.6V, discharge to 1.5V at 0.3C current, and repeat for 3 times;

[0037] S3: Cyclic voltammetry was used on the battery of S2 in an electrochemical workstation. The open circuit voltage was used as the starting point. The scan rate was set to 0.2 mV / s. In the voltage range of 1.5-4.6 V, a forward scan was performed once to a cut-off voltage of 4.6 V.

[0038] The electrochemical performance test was carried out, and the test parameters and results are shown in Table 1.

[0039] Embodiment 3:

[0040] S1 is the same as in Example 1;

[0041] S2: Charge the battery of S1 at 0.3C current, with a charging voltage range of 1.5-4.6V, and set four gradient voltages of 4.0V, 4.2V, 4.4V and 4.6V. The constant voltage durations are 15min, 15min, 30min and 15min respectively. After charging to a cut-off voltage of 4.6V, discharge to 1.5V at 0.3C current, and repeat once;

[0042] S3: Cyclic voltammetry was used on the battery of S2 in an electrochemical workstation. The open circuit voltage was used as the starting point. The scan rate was set to 0.5 mV / s. The voltage range was 1.5-4.6 V. The forward scan was performed twice until the cut-off voltage reached 4.6 V.

[0043] The electrochemical performance test was carried out, and the test parameters and results are shown in Table 1.

[0044] Embodiment 4:

[0045] S1 is the same as in Example 1;

[0046] S2: Charge the battery of S1 at 1.0C current, with a charging voltage range of 1.5-4.6V, set three gradient voltages of 4.2V, 4.4V and 4.6V, and set the constant voltage time to 30min, 15min and 30min respectively, and then discharge to 1.5V at 0.3C current, repeating 3 times;

[0047] S3: Cyclic voltammetry was used on the battery of S2 in an electrochemical workstation. The open circuit voltage was used as the starting point. The scan rate was set to 1.0 mV / s. The voltage range was 1.5-4.6 V. The forward scan was performed 3 times until the cut-off voltage reached 4.6 V.

[0048] The electrochemical performance test was carried out, and the test parameters and results are shown in Table 1.

[0049] Comparative Example 1:

[0050] S1 is the same as in Example 1, and S2 and S3 are omitted, and no activation experiment is performed. The test conditions are the same as in Example 4. The test parameters and results are detailed in Table 1.

[0051] Comparative Example 2:

[0052] S1 is the same as in Example 1, and S2 and S3 are omitted, and no activation experiment is performed. The test conditions are the same as in Example 1. The test parameters and results are detailed in Table 1.

[0053] Comparative Example 3:

[0054] S1 is the same as in Example 1;

[0055] S2: Cyclic voltammetry was used on the button cell of S1 in an electrochemical workstation. The open circuit voltage was used as the starting point. The scan rate was set to 1.0 mV / s. The voltage range was 1.5-4.6 V. The forward scan was performed 3 times until the cut-off voltage reached 4.6 V.

[0056] S3 was omitted and the electrochemical performance test was directly carried out. The test conditions were the same as those in Example 1. The test parameters and results are detailed in Table 1.

[0057] Comparative Example 4:

[0058] S1 is the same as Example 1, S2 is omitted, and S3 is performed directly: the button battery of S1 is charged with a current of 0.3C to a cut-off voltage of 4.6V, the constant voltage is maintained for 60 minutes, and then discharged with a current of 0.3C, and repeated 3 times.

[0059] The test conditions are the same as those in Example 1. The test parameters and results are detailed in Table 1.

[0060] Electrochemical performance test:

[0061] The electrochemical performance of Examples 1-4 and Comparative Examples 1-4 was tested. Specific test method: voltage range 1.5-4.6V, charge and discharge current 0.3C, cycle test 100 times, test results are shown in Table 1.

[0062] Table 1: Electrochemical performance test table of Examples 1-4 and Comparative Examples 1-4

[0063]

[0064] As can be seen from Table 1, Examples 1-4 all exhibited an initial discharge capacity of 108-131 mAh / g. After 100 cycles, the discharge capacity remained above 97 mAh / g, and the capacity retention rate was above 84%, showing performance equivalent to that of lithium-based silicate positive electrode materials. Figure 3 This is a charge and discharge curve diagram of 100 times of a lithium-source-free lithium-ion battery after activation of the sodium-based silicate material of Example 2. Figure 4 The charge and discharge curves of the lithium-free lithium-ion battery after activation of the sodium-based silicate material in Example 4 are shown in FIG. Figure 3 and Figure 4 It can be seen that the charge and discharge curves of Example 2 and Example 4 are regular, the cycles are normal, and there is no disorder.

[0065] Figure 5 The first two charge and discharge curves of the lithium-ion battery without lithium source and without activated sodium-based silicate material in Comparative Example 1 are shown. Figure 5 It can be seen that in Comparative Example 1 which was not activated by the present invention, the curves were disordered during the initial two charging processes and the cycle could not be normal, which was related to the fact that the sodium ions in the active material could not be smoothly released.

[0066] Figure 6 The figure is a charge-discharge curve of 100 times of the sodium-based silicate material lithium-ion battery without lithium source treated with only cyclic voltammetry in Comparative Example 3. Figure 6 It can be seen that the coulombic efficiency of comparative example 3 is relatively high, but the capacity attenuation is serious. After 100 charge and discharge cycles, the discharge capacity is only 43 mAh / g. This result indicates that after cyclic voltammetry treatment, a phase interface passivation film with a certain stability is formed on the surface of the material, but the sodium ion extraction efficiency in the bulk phase is not good, which reduces the capacity of the material.

[0067] Comparative Example 4 is a sample that has only undergone constant voltage charging. Compared with the example that has undergone step charge and discharge and cyclic voltammetry complete activation, the charge and discharge specific capacity is lower and the capacity decay is faster. Compared with Example 1 that has undergone step charge and discharge and cyclic voltammetry complete activation, the discharge capacity is 30-70 mAh / g lower, which is related to the instability of the interfacial SEI film caused by the lack of cyclic voltammetry step.

[0068] In summary, the activation method of the present invention can fully remove the sodium ions in the sodium-based silicate, which is helpful to form a stable and high-quality SEI film, so that the sodium-based silicate material can be used as the positive electrode of a lithium-free lithium-ion battery.

[0069] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for activating a sodium-based silicate material as a positive electrode of a lithium-ion battery without a lithium source, characterized in that: The specific activation steps are: S1: Mix the sodium-based silicate material, conductive agent and binder evenly, add N-methylpyrrolidone, stir thoroughly to form a slurry, evenly coat it on aluminum foil, and assemble it into a button battery after drying as the positive electrode and the metal lithium sheet as the negative electrode; S2: charge with current I1, voltage range V1-V2, set x step voltages between V1-V2, constant voltage time of each step voltage is T1, then discharge with current I1, repeat n1 times; S3: The battery after S2 is subjected to cyclic voltammetry in an electrochemical workstation, with the open circuit voltage as the starting point, a scan rate of γ1 is set, and a forward scan is performed n2 times in the voltage range of V3-V4 to a cut-off voltage of V4.

2. The method according to claim 1, characterized in that The general structural formula of the sodium-based silicate material in S1 is Na2MSiO4, wherein M is at least one of Fe, Mn, Al, Co, Ni, Ti, Cu, Mg or Zn.

3. The method according to claim 1, characterized in that The mass ratio of the sodium-based silicate material, the conductive agent and the binder in S1 is 5-20:1-2:

1.

4. The method according to claim 1, characterized in that: In S2, 0.2C≤I1≤2C, 1.5V≤V1<V2≤5.0V.

5. The method according to claim 1, characterized in that In S2, T1 is 15-60min.

6. The method according to claim 1, characterized in that In S2, 1≤n1≤3, 2≤x≤4.

7. The method according to claim 1, characterized in that In S3, 0.1mV / s≤γ1≤5mV / s, 1.5V≤V3≤2.0V, 4.0V≤V4≤4.8V.

8. The method according to claim 1, characterized in that In S3, 1≤n2≤5.

9. A lithium-ion battery positive electrode material without a lithium source, characterized in that: The sodium-based silicate material according to any one of claims 1 to 8 is prepared by a method for activating the positive electrode of a lithium-ion battery without a lithium source.

10. Use of the lithium-source-free lithium-ion battery positive electrode material according to claim 9 in a lithium-source-free lithium-ion battery.

Citation Information

Patent Citations

  • Lithium ion battery in-situ pre-lithiation method and lithium ion battery

    CN109671999A

  • Activation method of lithium ion battery containing lithium-rich manganese-based material and obtained lithium ion battery

    CN113871737A

  • Preparation method of electrochemical pre-lithiation MXene negative electrode

    CN115763712A

  • Sodium transition metal silicates

    US20170155150A1

  • Pre-embedding agent, pre-embedded lithium positive electrode, pre-embedded sodium positive electrode, secondary battery comprising same, method for pre-embedding lithium, and method for pre-embedding sodium

    WO2024212829A1